2018
DOI: 10.3897/zookeys.786.28539
|View full text |Cite
|
Sign up to set email alerts
|

A new genus and species of clingfish from the Rangitāhua Kermadec Islands of New Zealand (Teleostei, Gobiesocidae)

Abstract: Flexorincus, new genus and species, is described from 15 specimens (14.0–27.2 mm SL) collected from shallow (0–9 meters) intertidal and sub-tidal waters of the Rangitāhua Kermadec Islands, New Zealand. The new taxon is distinguished from all other members of the Gobiesocidae by a combination of characters, including a heterodont dentition comprising both conical and distinct incisiviform teeth that are laterally compressed with a strongly recurved cusp, an oval-shaped opening between premaxillae, a double adhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 33 publications
(39 reference statements)
1
13
0
Order By: Relevance
“…Although early biogeographic descriptions of the fish fauna suggested that subtropical fish taxa have more restricted ranges in the South-west Pacific (Francis 1993), whereas the fish fauna of South-eastern Pacific was biogeographically cohesive, recent studies have revealed cryptic lineages and endemic species within the South-eastern Pacific region (e.g. Hoese and Stewart 2012;Conway et al 2018;Delrieu-Trottin et al 2018). Notably, the closest relatives of several species (and clades) endemic to Rapa Nui are found in Rangita ¯hua (the Kermadec Islands; Delrieu-Trottin et al 2018), and not the intervening predominantly tropical islands of French Polynesia.…”
Section: Introductionmentioning
confidence: 99%
“…Although early biogeographic descriptions of the fish fauna suggested that subtropical fish taxa have more restricted ranges in the South-west Pacific (Francis 1993), whereas the fish fauna of South-eastern Pacific was biogeographically cohesive, recent studies have revealed cryptic lineages and endemic species within the South-eastern Pacific region (e.g. Hoese and Stewart 2012;Conway et al 2018;Delrieu-Trottin et al 2018). Notably, the closest relatives of several species (and clades) endemic to Rapa Nui are found in Rangita ¯hua (the Kermadec Islands; Delrieu-Trottin et al 2018), and not the intervening predominantly tropical islands of French Polynesia.…”
Section: Introductionmentioning
confidence: 99%
“…We have also found characters of the cephalic lateral-line canal system useful for the purpose of diagnosing Flabellicauda relative to other genera of the Diademichthyinae and also for diagnosis of the different members of the genus. In all four species of Flabellicauda, the preoperculo-mandibular lateral-line canal is absent, and this character, in combination with others, is useful to distinguish the new genus from the other diademichthyine genera that possess this structure (e.g., the preopercle houses a canal in Aspasma, Diademichthys, Flexor, Lepadichthys, Pherallodichthys, and Propherallodus; Shiogaki and Dotsu, 1983;Conway et al, 2018a;Motomura, 2019b, 2020b). There is also variation in the infraorbital and otic lateral-line canal among the four members of Flabellicauda.…”
Section: Discussionmentioning
confidence: 99%
“…The most common condition of the hypobranchial elements in gobiesocids is for all three to be present and ossified (e.g., see Springer and Fraser 1976: Fig. 4b) although other conditions exist, including one in which all three hypobranchial cartilages are present but only the first is ossified as hypobranchial 1 (e.g., see Conway et al 2018: Fig. 8C) and another in which the first element is absent and the second and third elements are present and ossified as hypobranchials 2 and 3, respectively (as in Alabes ; see Springer and Fraser 1976: Fig.…”
Section: Discussionmentioning
confidence: 99%